Shelter of the most high - Cossette, Connilyn (Cities of refuge, 2018)
"Captured by raiders in 1388 B.C., Sofea narrowly escapes slavery. Bargaining her way to a city of refuge in Israel, she finds herself in more danger. Can she find safety in this city of strangers, accept their God as hers, and be satisfied with His justice instead of her own?"--